Analysis of the role of the low threshold currents IT and Ih in intrinsic delta oscillations of thalamocortical neurons - Amarillo Gomez, Yimy; Mato, German; Nadal, Marcela (Frontiers Media S.A., 2015)
Fil: Amarillo Gomez, Yimy. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina